Emission of exhaust system (exhaust pollutant) / Ahmad Muzahar Abdul Muhaimin and Suhaimi Ihwan - Abdul Muhaimin, Ahmad Muzahar; Ihwan, Suhaimi (2001)
Pollution is a well-known thing that can destroy the environment. Therefore, this project, which is more to vehicle exhaust emission, will tell what, how the pollution create by this system. First, the pollutant and the formation of pollutant are studied. Research was made to get information about emission system and pollutant. Furthermore, gases are studied. In addition, studied was made at PUSPAKOM. At PUSPAKOM we got to know how to detect and read the emission of the exhaust system and what are the cause of the emission if not in the specific level and what are the specific level. Furthermore, what are the adjustment must be done is recognized. Then, types of vehicle are explained and how is the engine works or operates and what are the products of emission. Finally, minimizing the pollution create by vehicles so that it will be environmentally friendly.